Stories, identities, and political change - Tilly, Charles (Lanham Rowman & Littlefield, 2002)
Tilly's newest book tackles fundamental questions about the nature of personal, political, and national identities and their linkage to big events―revolutions, social movements, democratization, and other processes of political and social change. Tilly focuses in this book on the role of stories, as means of creating personal identity, but also as explanations, true or false, of political tensions and realities. He uses well-known examples from around the world―the Zapatista rebellion, Hindu-Muslim conflicts, and other examples in which nationalism and other forms of group identity are politically pivotal. Tilly writes with the immediacy of a journalist, but the profound insight of a great theorist.
Includes bibliographical references (p. 213-243) and index.
Keywords: Social conflict